Practitioner perspectives on strategies to promote longer-term benefits of acupuncture or counselling for depression: a qualitative study. - Hugh MacPherson; Liz Newbronner; Ruth Chamberlain; Stewart J Richmond; Harriet Lansdown; Sara Perren; Ann Hopton; Karen Spilsbury (PLoS ONE)
Background Non-pharmacological interventions for depression may help patients manage their condition. Evidence from a recent large-scale trial (ACUDep) suggests that acupuncture and counselling can provide longer-term benefits for many patients with depression. This paper describes the strategies practitioners reported using to promote longer-term benefits for their patients. Methods A qualitative sub-study of practitioners (acupuncturists and counsellors) embedded in a randomised controlled trial. Using topic guides, data was collected from telephone interviews and a focus group, altogether involving 19 counsellors and 17 acupuncturists. Data were audio recorded, transcribed verbatim and analysed using thematic content analysis. Results For longer-term impact, both acupuncturists and counsellors encouraged insight into root causes of depression on an individual basis and saw small incremental changes as precursors to sustained benefit. Acupuncturists stressed the importance of addressing concurrent physical symptoms, for example helping patients relax or sleep better in order to be more receptive to change, and highlighted the importance of Chinese medicine theory-based lifestyle change for lasting benefit. Counsellors more often highlighted the importance of the therapeutic relationship, emphasising the need for careful "pacing" such that the process and tools employed were tailored and timed for each individual, depending on the "readiness" to change. Our data is limited to acupuncture practitioners using the principles of traditional Chinese medicine, and counsellors using a humanistic, non-directive and person-centred approach. Conclusions Long-term change appears to be an important focus within the practices of both acupuncturists and counsellors. To achieve this, practitioners stressed the need for an individualised approach with a focus on root causes.